1996
DOI: 10.1007/bf00346609
|View full text |Cite
|
Sign up to set email alerts
|

Isolated trigeminal neuralgia secondary to distal anterior inferior cerebellar artery aneurysm

Abstract: A 43-year-old woman complaining of severe pain of the right side of the face was admitted to the Department of Neurosurgery. It had been present for three months and diagnosed as trigeminal neuralgia. The CT scan without contrast material had been considered normal at that time. Three months later, after a favourable response to carbamazepine, she suddenly developed right occipital headache and drowsiness. On admission, she was alert, and neurological examination revealed only mild neck stiffness. Computed tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 20 publications
0
26
0
6
Order By: Relevance
“…Some authors have reported TGN caused by the conflict with aneurysms on the anterior inferior cerebellar artery (AICA), posterior communicating artery and basilar artery (BA) [4,10,13,20,26,27,29]. In most publications there was not isolated idiopathic neuralgia, but the effect of compres- …”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported TGN caused by the conflict with aneurysms on the anterior inferior cerebellar artery (AICA), posterior communicating artery and basilar artery (BA) [4,10,13,20,26,27,29]. In most publications there was not isolated idiopathic neuralgia, but the effect of compres- …”
Section: Discussionmentioning
confidence: 99%
“…A few cases of thrombosed large AICA aneurysm have been reported, 1,6,7,11,13,16) including local association with acute hematoma. 6,16) One patient complained of sudden onset of occipital headache, nausea, and vomiting, 6) and the other patient suddenly developed facial numbness and headache.…”
Section: Discussionmentioning
confidence: 99%
“…6,16) One patient complained of sudden onset of occipital headache, nausea, and vomiting, 6) and the other patient suddenly developed facial numbness and headache. 16) The sudden onsets of symptoms indicated rupture of an aneurysm in these cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,17) These symptoms result from compression of cranial nerves or the brainstem, and may be prodromal signs of rupture. 4,17) The clinical and neuroimaging features of this unusual lesion have been discussed, but the pathological features and surgical issues have never been thoroughly exam- We report three cases of distal AICA aneurysm manifesting as SAH, and describe direct surgical observations of the vascular structures.…”
Section: Introductionmentioning
confidence: 99%